1998
DOI: 10.1080/1360144980030207
|View full text |Cite
|
Sign up to set email alerts
|

How six outstanding math professors view teaching and learning: The importance of caring

Abstract: Six exemplary professors, all trained as mathematicians, were interviewed regarding their views about university teaching and learning. Nine themes emerged; seven related to teaching and two related to learning. Among the teaching themes, the most prominent was the importance placed on caring and concern for students. In addition the professors were concerned with all essential aspects of course design (content, learning outcomes, strategies and evaluation), passion for their discipline and their teaching, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Such a vision of teaching is articulated by Rendón (2009) as 'sentipensante pedagogy' that involves the ability to see the connections between seeming opposites, such as thinking and feeling. Within these studies, it appears that caring teachers appear to be motivated to do all that is possible to maximize a student's chance of success and the literature attests to the means by which individual teachers carefully articulate and precisely fashion their caring philosophies and practices (Larson, 2006;Noddings, 1999;O'Connor, 2008;Weston and McAlpine, 1998;Zembylas, Bozalek and Shefer, 2014). However, there are limitations within the current research, and these lead to an imperfect understanding of the nature of pedagogic care, the distinctions between care in practice and the rationales and motivations of teachers who care, particularly in higher education.…”
mentioning
confidence: 99%
“…Such a vision of teaching is articulated by Rendón (2009) as 'sentipensante pedagogy' that involves the ability to see the connections between seeming opposites, such as thinking and feeling. Within these studies, it appears that caring teachers appear to be motivated to do all that is possible to maximize a student's chance of success and the literature attests to the means by which individual teachers carefully articulate and precisely fashion their caring philosophies and practices (Larson, 2006;Noddings, 1999;O'Connor, 2008;Weston and McAlpine, 1998;Zembylas, Bozalek and Shefer, 2014). However, there are limitations within the current research, and these lead to an imperfect understanding of the nature of pedagogic care, the distinctions between care in practice and the rationales and motivations of teachers who care, particularly in higher education.…”
mentioning
confidence: 99%
“…Yet despite this apparent reluctance to speak of love, the centrality of care and love is evident in past educational research. For example, Weston & McAlpine (1998) found that the category of caring they identified through their interviews of mathematics professors included a combined theme summarized as "care for, respect, love students." And, similarly, our interviewees frequently spoke about loving their time with students or how they loved getting to know them.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are also very much in keeping with findings from an interview study of six exemplary mathematics professors. In this case, Weston & McAlpine (1998) found that nine categories emerged from their interview study with the most salient category that emerged being the importance placed on caring and concern for students.…”
Section: Discussionmentioning
confidence: 99%